2021
DOI: 10.1080/24694452.2021.1956876
|View full text |Cite
|
Sign up to set email alerts
|

What Is Essential Travel? Socioeconomic Differences in Travel Demand in Columbus, Ohio, during the COVID-19 Lockdown

Abstract: The COVID-19 pandemic has profoundly reshaped urban mobility. During the lockdown, workers teleworked if possible and left home only for essential activities. Our study investigates the spatial patterns of essential travel and their socioeconomic differences during the COVID-19 lockdown phase in comparison with the same period in 2019. Using data from Columbus, Ohio, we categorized travelers into high, moderate, and low socioeconomic status (SES) clusters and modeled travel demand of SES clusters for both phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…The unconstrained gravity‐type spatial interaction model (Gravity SI) described in Section 2.3 is perhaps the most widely used model for diverse types of aggregate transport flows (for several recent examples see Kar et al., 2021; Lenormand et al., 2016; Oshan, 2020; Zhou et al., 2020). It is calibrated here using a log‐linear Poisson regression with a power distance‐decay function and a set of origin/destination attributes using the spint module of the Python Spatial Analysis Library (PySAL) (Oshan, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The unconstrained gravity‐type spatial interaction model (Gravity SI) described in Section 2.3 is perhaps the most widely used model for diverse types of aggregate transport flows (for several recent examples see Kar et al., 2021; Lenormand et al., 2016; Oshan, 2020; Zhou et al., 2020). It is calibrated here using a log‐linear Poisson regression with a power distance‐decay function and a set of origin/destination attributes using the spint module of the Python Spatial Analysis Library (PySAL) (Oshan, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The former group usually explains trip generation, such as labor force (Pourebrahim, Sultana, Thill, & Mohanty, 2018;Signorino et al, 2011); GDP (Zhang, Cheng, & Jin, 2019) and human activity density (Marrocu & Paci, 2013). The latter are common destination determinants of travel demand, such as amenities (e.g., school, hospitals, markets) (Botella, Gora, Sosnowska, Karsznia, & Querol, 2021;Kar et al, 2021), tourism attractions (e.g., hotel rooms) (Khadaroo & Seetanah, 2008), and land-use types (Liu, Kang, Gong, & Liu, 2016).…”
Section: Spatial Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lockdowns and restrictions that were introduced had a differential impact on the mobility of populations, with unequal movement observed by both neighborhood deprivation and socioeconomic status (Campbell et al, 2021 ). In terms of the spatial structure of travel demand, Kar et al ( 2021 ) found in the United States that diffused travel patterns of individuals of higher and moderate socioeconomic status were found to have become more localized during the pandemic, while the pre-existing localized travel patterns of low socioeconomic status populations became diffused. The curtailing of movement through lockdowns and restrictions on travel appeared to exacerbate underlying social and spatial inequalities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have identified the impact of such measures on the transport sector by analyzing the effect on traffic demand and travel behavior ( Dingil and Esztergár-Kiss, 2021 , Patra et al, 2021 ), traffic safety ( Yasin et al, 2021 , Saladié et al, 2020 , Lin et al, 2021 , Shokouhyar et al, 2021 ), travelers’ attitudes ( Ceccato et al, 2021 , De Vos, 2020 , Kar et al, 2021 , Brough et al, 2021 , Zhang et al, 2021 ), and impact on air quality and environment ( Singh and Chauhan, 2020 , Nakada and Urban, 2020 , Zangari et al, 2020 , Benchrif et al, 2021 , Polednik, 2021 , Xin et al, 2021 ). However, this study differs from the existing literature by investigating the correlation between the pandemic's response measures and urban traffic flows and then employing such a relationship in estimating traffic flows under different conditions in the future.…”
Section: Study Motivationsmentioning
confidence: 99%